(3OQI GdJGL ef TYQ GHf GdMLGLs - (3CHh GdbGSe gHI Gddg Hf GdMSf Hf CMeO GdEUWQdGHj GdHOjY,J (B534 (3g` s ((3GdTjN CHh eMeO GdNTGH s)
(3ChdgG (B:s
(3bGd CejQ GdeDefjf YeQ Hf GdNWGH QVj Gddg Yfg(B: (3dG HCS HGdCHjGJ ef GdTYQ jbOegG GdQLd Hjf jOi MGLJg jSJYWa HgG GddFje hjSJfRd HgG GdcQje s
(3BNQgG (B:s
(3GdHGH GdeGFI hGdMGOj hGdCQHYhf aj GdOYGA def CMS NhakG hSjO djS dj LGg aCHPdg dg, hdG aj jOj eGd aCYWjg LgOj GdOYGA dg s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCgdjI HHGQjS (B(5913) s
Keywords: (3GdCOHs